« Women and/in the Holocaust » : à la croisée des Women’s-Gender et Holocaust Studies (Années 1980-2010) - Isabelle Ernot (Genre & Histoire)
The focus on Jewish women during the Holocaust emerged from feminist research in the early 1980s in the United States. This interdisciplinary strand of history has been subject to some serious criticism. While the sub-discipline has developed in Israel, the United States, Germany and Britain, it has been ignored in the western European countries principally affected by the Shoah. As well as investigating the origins and main areas of focus of the sub-discipline, this article explores the conflicts that lie at its heart, notably between notions of ‘race’ and ‘sex’, and questions the limits of women’s and gender history in the study of genocide.